Exploring the role of Yuxuebi tablet in neuropathic pain with the method of similarity research of drug pharmacological effects based on unsupervised machine learning - Du, Xiao; Zhao, Chunhui; Xi, Yujie; Lin, Pengfei; Liu, Huihui; Wang, Shuling; Guo, Feifei (Frontiers in Pharmacology, 2024)
Having multiple pharmacological effects is a characteristic of Traditional Chinese Medicine (TCM). Currently, there is a lack of suitable methods to explore and discover modern diseases suitable for TCM treatment using this characteristic. Unsupervised machine learning technology is an efficient strategy to predict the pharmacological activity of drugs. This study takes Yuxuebi Tablet (YXB) as the research object. Using the unsupervised machine learning technology of drug cell functional fingerprint similarity research, the potential pharmacological effects of YXB were discovered and verified. First, LC-MS combined with the in vitro intestinal absorption method was used to identify 40 chemical components of YXB that could be absorbed by the intestinal tract of rats. Unsupervised learning hierarchical clustering was used to calculate the degree of similarity of cellular functional fingerprints between these components and 121 marketed Western drugs whose indications are diseases and symptoms that YXB is commonly used to treat. Then, based on the Library of Integrated Network-based Cellular Signatures database, pathway analysis was performed for selected Western medicines that have high similarity in cellular functional fingerprints with the components of YXB. We found that the components of YXB are pharmacologically very similar to non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids. Through prediction studies, we found that the intestinally absorbed components identified in YXB have high similarity to both NSAIDs and adrenocortical hormones in their pharmacological effects. In addition, they were also found to have very similar pharmacological effects to anti-neuropathic pain drugs (such as gabapentin, duloxetine, and pethidine) and may inhibit the NF-κB signaling pathway and biological processes related to pain perception. Therefore, YXB may have anti-neuropathic pain effects. Finally, we demonstrated that YXB significantly reduced neuropathic pain in a rat model of sciatic nerve chronic constriction injury (CCI). Transcriptome analysis further revealed that YXB regulates the expression of multiple genes involved in nerve injury repair, signal transduction, ion channels, and inflammatory response, with key regulatory targets including Sgk1, Sst, Isl1, and Shh. In conclusion, this study successfully identified and confirmed the previously unknown pharmacological activity of YXB against neuropathic pain through unsupervised learning prediction and experimental verification.